ANALISIS PENDAPATAN DAN EFISIENSI USAHATANI PADI SAWAH MELALUI SISTEM SUBAK PADA SUBAK PURA SARI DI KOTA BAUBAU - Ajo, Antasalam (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2017)
Abstract   The thing rises of the Balinese-Hindu farmers in the implementation of the Subak system in their fields. In this system, common life is arranged among farmers, where the irrigation system is carried out fairly and evenly, all problems are discussed together such as determining the planting tune, and the type of rice to be planted. If there is a violation, the sanction is determined through a civil ceremony or ritual held in Pura. This study aims to determine the income of lowland rice farmers who implemented the Subak system in the Subak Pura Sari in Baubau Town. The results showed that the average income of lowland rice farming that implemented the Subak system in Baubau Town was IDR 12,767,352 in the form of rice per planting season, with an average cost of IDR 9.162,648 in the period from 2016 to 2017. While in terms of efficiency, farming is profitable because the R/C ratio is greater than 1, namely 1.39. Fulfillment of the needs of farmers with this income is considered because the number of regional minimum wages (UMR) in Southeast Sulawesi in 2017 is at the figure of IDR 2,002,625 per month.   Keywords: Subak system, rice fields, farm income